A gest??o do Programa Nacional de Alimenta????o Escolar: o direito ?? alimenta????o para estudantes da educa????o especial do Distrito Federal - Castro, Solange Fernandes de Freitas (2017)
This present dissertation is the result of a research carried out with the Stricto Sensu Post- Graduation Program in Education of the Catholic University of Brasilia, in the area of Political Concentration and Administration of Education and in the line of research, Politics, Management and Economics of Education. This research investigated the National School Feeding Program (PNAE) management in public schools from Distrito Federal which offer Specialized Educational Assistence (AEE) for prescholar, regarding aspects of financing, the management performance of the nutritionist during elaborating, executing and monitoring menus and pedagogical actions carried out by schools within the scope of the Program. A comparative method was adopted as a guideline in order to reach the proposed objectives, being essentially qualitative, without neglecting the quantitative data. For this, two school units were selected from the Administrative Region with the largest number of schools in the public system that performs AEE for prescholars. Two schools were selected among five schools with the highest number of pre-school students in specialized care: the one with the highest number of pre-school students in AEE and the one with the smallest amount. The data colected through interviews were submitted to content analysis technique, and a comparative analysis was based on a tool in order to identify the level of similarity/difference between the schools, identifying the causes involved and their interrelationships. It was found that there is no nutritional diagnosis and health status monitoring of special education students, nor elaboration of differentiated menus for this teaching modality. SEEDF receives a different and duplicated per capita from the federal government to attend school meals during 200 school days for students enrolled in the AEE. However, in the schools observed students received only one meal during the period of schooling because they were not attended in two periods. It was verified that food and nutrition topics were not contemplated in the political pedagogical projects of the schools. It concludes that those involved in the management of the PNAE in Distrito Federal must find viable ways to guarantee the right to adequate and healthy food, in the conception of an inclusive and equitable education for all students with disabilities and to incorporate pedagogical actions in the school curriculum.